Hematopoietic cell transplantation in inborn errors of immunity Part I: severe combined immunodeficiency - Muratori, Rafaella; Fernandes, Juliana Folloni; Loth, Gisele; Vieira, Ana Karine; Klinger, Paulo; Franco, Simone; Bonfim, Carmem (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Severe Combined Immunodeficiencies (SCID) are rare diseases characterized by a blockage in T-lymphocyte development. Hematopoietic Cell Transplantation (HCT) is the primary curative therapy, with the highest survival rates correlated to early diagnosis and the absence of active infections at transplant. The gold standard is a matched related sibling donor (MSD), but alternative donors like haploidentical family donors are increasingly used. Conditioning regimens vary, with reduced intensity busulfan and fludarabine often indicated. Early diagnosis via newborn screening and referral to experienced HCT centers are crucial for improving outcomes. Long-term follow-up is essential, as the cumulative incidence of late effects, such as neurologic and neurodevelopmental issues, increases over time.